Use of medium cut-off membrane dialyzer compared to high flux membrane dialyzer in improving the clearance of middle to large molecule uremic toxins: A Systematic Review - Wasal Desrial Siregar; Krisna Yetti; Agung Waluyo; yulia yulia (Malahayati International Journal of Nursing and Health Science, 2025)
Background: The loss of kidney function in patients with kidney disease leads to the accumulation of dissolved substances known as uremic toxins, which can negatively impact patient health. Membranes with a high number of pores, such as those in high-flux dialyzers, allow some medium-sized molecules like beta-2 microglobulin to pass through. However, these membranes are less effective at filtering out larger dissolved substances. Larger medium-sized molecules (>25 kD) need to be removed either by convection or through the use of highly permeable membranes such as Medium Cut-Off (MCO) membranes. Therefore, it is important to understand the improvement in uremic toxin clearance when using MCO dialyzers compared to high-flux dialyzers. Purpose: To evaluate and compare the effectiveness of using medium cut-off (MCO) membrane dialyzer with high flux membrane dialyzer. Method: A systematic review with article selection guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The systematic review process begins with the formulation of clinical questions relevant to the topic. Before this, the authors establish PICOS criteria, which stand for: P (problem, patient, or population), I (intervention, prognostic factor, or exposure), C (comparison or control), O (outcome), and S (study design). For this article, P: Patients with chronic kidney disease undergoing hemodialysis, I: Use of dialyzers with medium cut-off (MCO) membrane, C: Use of dialyzer with high flux membrane, O: Increased clearance of uremic toxins of middle to large molecules, such as β2-microglobulin, kappa and lambda free light chains, S: Randomized controlled trials. The article search was conducted systematically using the keywords: "Medium cut-off dialyzer" AND "High flux dialyzer" AND "Uremic toxins" AND "Middle molecules" AND "Large molecules" AND "Clearance Hemodialysis". Results: The use of MCO membranes was more effective in eliminating medium-to-large uremic toxins while maintaining safety and regulation comparable to conventional hemodialysis with high-flux dialyzers. MCO membranes were also more effective even with low blood flow, without significantly increasing albumin loss. Additionally, MCO membranes contributed to reducing inflammation and allowed for shorter recovery times post-hemodialysis treatment. Conclusion: Given its comparable safety to high-flux dialyzers, the use of MCO membranes can be expanded in clinical practice at hemodialysis centers, including those in resource-limited settings.